Penerokaan persediaan kerjaya Kaunselor secara professional dan personal dalam kalangan Kaunselor Pelatih Universiti Malaysia Sarawak - Fatin Zulaikha, Mohd Zulkifli (Universiti Malaysia Sarawak (UNIMAS), 2019)
Counselor trainer is often said to be nervous, lack of theoretical counseling knowledge, lack of skill and lack of confidence in conducting counseling sessions. Therefore, this qualitative study has been carried out to explore preparation of self-confidence, counseling knowledge and counseling skills professionally and personally on counseling career among 4th year counseling students of Universiti Malaysia Sarawak. Six interviewed interviewees consisted of two men and four women. In addition, from the findings, 15 subthemes, eight themes and three domains have been developed, for example, the subthemes produced are university learning, learning from counseling programs, theories practiced, and the theories used by trainee counselors in providing counseling services. Domain analysis has been used for data analysis purposes. Theimplication of this study can help trainee counselors and registered counselors for selfesteem and always enhance themselves with new issues and counseling skills. Next, this research also helps the trainee counselor to make an earlier plan when faced with a challenge in handling counseling issues especially when already in the organization